Materialists perceive their high socioeconomic status as justice: Associations with increased political participation - Zhirui Zhao; Qi Zhao; Su Tao; Wenchong Du (PLoS ONE, 2025)
Existing research has not reached a consensus on the relationship between subjective socioeconomic status (SSS) and political participation. Thus, this study investigated the psychological variables influencing the relationship between SSS and political participation. Specifically, it explored the mediating role of perceived social justice and the moderating role of materialism value. A sample of 1306 college students was conducted with the MacArthur Scale of SSS, the System Justification Scale, the Material Value Scale, and the Political Participation Behavior Scale. The results showed that: (1) There was a significant positive correlation between SSS, perceived social justice and political participation; materialism value shows a significant negative correlation with SSS, perceived social justice, and political participation. (2) Perceived social justice played a mediating role in the effect of SSS on political participation. (3) Materialism value moderated the relationship between SSS and perceived social justice. Under high materialism value, perceived social justice increases with SSS; however, under low materialism value, this effect is no longer significant. The study enriches our understanding of the underlying psychological mechanisms and marginal effects in the relationship between SSS and political participation.